`Out of sight, out of mind': absence of groundwater in water allocation of Narmada basin - Ranade, Rahul (2005)
The Narmada is one of the few rivers in India where clear-cut allocation of river water between participant states has been decreed by a central tribunal. The Narmada Water Disputes Tribunal's (NWDT) order issued in 1979 has since been the reference point for all water development plans in the basin. The aspect of this order that this paper focuses on is the lack of any reference to groundwater when fixing allocation between the party states. It is a well-documented fact that conditions of heavy groundwater extraction often lead to decline in stream flows. This report is a critique of the premise on which the NWDT has fixed the inter-state allocation; it argues that the omission of groundwater withdrawals in the tribunal award is a serious oversight which may result in forced deviations most other river basins in India - surface water allocation alone is inadequate if corresponding allocation of groundwater is not done. - Reproduced.
Keywords: Groundwater - India; Groundwater